2023
DOI: 10.9734/cjast/2023/v42i254182
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Public Health Significance of Hydatidosis: A Review

C. Mathivathani,
V. J. Ajaykumar,
C. Angeline Felicia Bora

Abstract: Echinococcus granulosus is an important dog tape worm whose larval stage causes hydatidosis in animals and man. The objective of this review on hydatidosis is to get a comprehensive knowledge about the disease and it had included the data of past 10 years collected from various scientific articles. Food animals such as sheep, goat, cattle etc. act as its intermediate host. It is a major parasitic zoonosis having high economic loss and public health significance and high worldwide prevalence rate. There are dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Despite this, developing countries continue to have a high prevalence of CE, especially in rural regions, cystic echinococcosis (CE ( is diagnosed, the quality of illness management and treatment can be significantly improved [5]. This study found that the sero-prevalence of cystic echinococcosis by ELISA using Ps.C antigen was 43.65% in random human sera and 59.78% in random camel sera.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite this, developing countries continue to have a high prevalence of CE, especially in rural regions, cystic echinococcosis (CE ( is diagnosed, the quality of illness management and treatment can be significantly improved [5]. This study found that the sero-prevalence of cystic echinococcosis by ELISA using Ps.C antigen was 43.65% in random human sera and 59.78% in random camel sera.…”
Section: Discussionmentioning
confidence: 94%
“…It has been established that serological immunological molecular assays are helpful not only in the initial diagnosis of infection in humans and animals but also in improving the quality of disease management and in monitoring patients following surgery or other treatments [4]. The socio-economic impact is considerably high since both man and livestock are involved as intermediate hosts [5]. The economic losses in animal production as lowered meat, milk and wool production and health hazard along with treatment costs of cystic echinococcosis in man are enormous [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hydatidosis is a parasitic disease that has significant consequences for both Veterinary Medicine and public health worldwide (Mathivathani et al, 2023). The disease is caused by the metacestode larval stage or hydatid cyst of the tapeworm Echinococcus granulosus, which belongs to the family Taeniidae (El Hassan and El-Bahr, 2022).…”
Section: Introductionmentioning
confidence: 99%